2022
DOI: 10.1097/hs9.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Isatuximab With Pomalidomide and Dexamethasone in Relapsed Myeloma: Results of a UK-Wide Real-World Dataset

Abstract: Real-world data on the efficacy and tolerability of isatuximab with pomalidomide and dexamethasone (IsaPomDex) in relapsed/refractory myeloma patients have not been reported. In this UK-wide retrospective study, IsaPomDex outcomes were evaluated across 24 routine care cancer centers. The primary endpoint was overall response rate (ORR). Secondary endpoints included progression-free survival (PFS), duration of response (DOR) for patients who achieved an objective response (≥partial response [PR]), and adverse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…9 Real-world outcomes of IsaPomDex in a UK-wide study showed that efficacy outcomes are comparable to trial data. 10 ICARIA-MM trial outcomes by frailty employed the simplified frailty score and demonstrated that overall response rate (ORR) was statistically higher with IsaPomDex compared to PomDex, regardless of frailty status: frail (52.1% vs. 34.2%, p = 0.0476), non-frail (66.3% vs. 35.7%, p < 0.0001), but the difference in the ORR rate between frail and non-frail patients receiving IsaPomDex was not statistically significant (p = 0.3971). Median PFS was higher with IsaPomDex compared to PomDex regardless of frailty status, but the difference was only statistically significant for the non-frail subgroup comparison: frail (9 vs. 4.5 months, p = 0.4928), non-frail patients (12.7 vs. 7.4 months, p = 0.0004).…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Real-world outcomes of IsaPomDex in a UK-wide study showed that efficacy outcomes are comparable to trial data. 10 ICARIA-MM trial outcomes by frailty employed the simplified frailty score and demonstrated that overall response rate (ORR) was statistically higher with IsaPomDex compared to PomDex, regardless of frailty status: frail (52.1% vs. 34.2%, p = 0.0476), non-frail (66.3% vs. 35.7%, p < 0.0001), but the difference in the ORR rate between frail and non-frail patients receiving IsaPomDex was not statistically significant (p = 0.3971). Median PFS was higher with IsaPomDex compared to PomDex regardless of frailty status, but the difference was only statistically significant for the non-frail subgroup comparison: frail (9 vs. 4.5 months, p = 0.4928), non-frail patients (12.7 vs. 7.4 months, p = 0.0004).…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Alexandros Rampotas 1,2 Grant Vallance 1 Fotios Panitsas 3 Nanda Basker 4 Gina Sangha 5 Beena Salhan 6,7,8,9 Farheen Karim 9,10 Firas Al-Kaisi 11 Amy Gudger…”
Section: On F L Ic T Of I N T E R E S T S Tat E M E N Tmentioning
confidence: 99%
“…11 The study reported an overall response rate (ORR) of 66.4%, and an mPFS of 10.9 months. 11 Isa-Pd is also being investigated in the non-interventional, multinational, observational IONA-MM study. 12 Prior to its approval, Isa was available in France under two early access programs (EAPs)-a nominative temporary authorization for use (nATU) issued by French authorities for each patient upon a physician's request for access, then a cohort temporary authorization for use (cATU) intended to include a cohort of eligible patients according to a defined protocol.…”
Section: Introductionmentioning
confidence: 97%
“…Real‐world data are complementary to clinical trial data and are needed to determine factors in real‐world practice that may impact efficacy and safety. Real‐world use of Isa‐Pd has been reported in a UK‐wide, real‐world dataset, which utilized medical records of RRMM patients from 24 centers in the United Kingdom who started therapy between January 2020 and May 2021, and received ≥1 cycle of Isa‐Pd 11 . The study reported an overall response rate (ORR) of 66.4%, and an mPFS of 10.9 months 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation